Whole Genome Identification of Potential G-Quadruplexes and Analysis of the G-Quadruplex Binding Domain for SARS-CoV-2 - Zhang, Rongxin; Xiao, Ke; Gu, Yu; Liu, Hongde; Sun, Xiao (Frontiers in Genetics, 2020)
The Coronavirus Disease 2019 (COVID-19) pandemic caused by SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) has become a global public health emergency. G-quadruplex, one of the non-canonical secondary structures, has shown potential antiviral values. However, little is known about the G-quadruplexes of the emerging SARS-CoV-2. Herein, we characterized the potential G-quadruplexes in both positive and negative-sense viral strands. The identified potential G-quadruplexes exhibited similar features to the G-quadruplexes detected in the human transcriptome. Within some bat and pangolin related betacoronaviruses, the G-tracts rather than the loops were under heightened selective constraints. We also found that the amino acid sequence similar to SUD (SARS-unique domain) was retained in SARS-CoV-2 but depleted in some other coronaviruses that can infect humans. Further analysis revealed that the amino acid residues related to the binding affinity of G-quadruplexes were conserved among 16,466 SARS-CoV-2 samples. Moreover, the dimer of the SUD-homology structure in SARS-CoV-2 displayed similar electrostatic potential patterns to the SUD dimer from SARS. Considering the potential value of G-quadruplexes to serve as targets in antiviral strategy, our fundamental research could provide new insights for the SARS-CoV-2 drug discovery. A preprint of this paper has been posted on bioRxiv [1].